The Effect of Grape Temperature on the Sensory Perception of Méthode Cap Classique Wines - Mafata, M.; Buica, A.; du Toit, W.; Panzeri, V.; van Jaarsveld, F.P. (South African Journal of Enology and Viticulture, 2018)
The production process of South African bottle-fermented sparkling wine, the Méthode Cap Classique (MCC), follows the traditional French method (méthode champenoise), although each cellar has its own unique additions to the method. South African winemakers use different techniques and blends to achieve their award-winning MCCs, but there have not been many scientific investigations of the science behind these wines. This project is one of the first scientific studies on MCC. MCC wines were made using Chardonnay and Pinot Noir grapes harvested over two vintages (2014 and 2015) from two regions (Robertson and Darling) and stored at 0°C, 10°C, 25°C and 30°C before processing. The study was aimed at investigating the effect of grape storage temperature on the sensory characteristics of MCCs. The aroma and taste of the final nine-month old MCCs were evaluated, with each region analysed separately. The study showed a grouping of the MCCs according to temperature treatments for both vintages. There were vintage differences in terms of the attributes cited and the frequency of citations. Based on the frequency of citation, the MCCs made 2014 from grapes stored at 0°C and 10°C were described by the judges as having a fruity, fresh and crisp aroma, whilst those made from grapes stored at 25°C and 30°C were described as having oxidised fruit, volatile acidity and solvent-like aromas. The judges perceived less oxidation and volatile acidity (VA) (in terms of the frequency of citation) in the aroma of the 2015 MCCs, although treatments at higher temperatures were still associated with less desirable attributes compared to treatments at lower temperature. This study shown that the temperature of the grape at the time of processing has a significant effect on the aroma of MCCs aged nine months, and not so much of an effect on the taste.